2023
DOI: 10.1111/petr.14520
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case–control study of gastrostomy use in children undergoing hematopoietic cell transplantation

Abstract: Background Maintaining a good nutritional status during the hematopoietic cell transplantation (HCT) procedure is challenging in the pediatric population. Methods In a multicentric retrospective study, we compared the outcome of nutritional status and HCT‐related parameters in 227 pediatric patients during and after HCT between 2005 and 2015. 112 patients received a gastrostomy before the start of HCT (GS group), and 115 did not receive a gastrostomy (NGS). Data collection was performed at HCT, 3, 6, and 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The studies varied with respect to when nutritional support was introduced, as well as the means to measure the ongoing nutritional status of the patients. Various ways to measure the overall nutritional status included food weighing and recording daily intake [ 37 ], daily weights [ 13 , 36 , 37 , 38 , 39 , 43 ], and the albumin level [ 13 , 36 , 37 ]. EN was typically started when patients were unable to meet more than 50% of their caloric needs over 2–3 days; however, some calculated this by the Holliday–Segar formula [ 41 ] and others by the Scientific Advisory Committee on Nutrition’s recommendations [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies varied with respect to when nutritional support was introduced, as well as the means to measure the ongoing nutritional status of the patients. Various ways to measure the overall nutritional status included food weighing and recording daily intake [ 37 ], daily weights [ 13 , 36 , 37 , 38 , 39 , 43 ], and the albumin level [ 13 , 36 , 37 ]. EN was typically started when patients were unable to meet more than 50% of their caloric needs over 2–3 days; however, some calculated this by the Holliday–Segar formula [ 41 ] and others by the Scientific Advisory Committee on Nutrition’s recommendations [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…PN was added in cases of severe mucositis, GI GVHD, NG-tube refusal, or intractable vomiting and/or diarrhea [ 13 , 36 , 37 , 41 ], or otherwise in cases of an inability to meet greater than 50% of their caloric needs by EN support [ 37 ]. In studies that utilized prophylactic G-tube placement, one study found that, on average, the surgery occurred around 46 days prior to BMT admission [ 43 ], but in others, this timing was not noted [ 37 , 38 , 39 , 41 ]. When noted, NG-tubes were placed from day − 2 to day + 2 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations